PENGARUH DISKUALITAS PELAYANAN TERHADAP NEGATIVE WORD OF MOUTH (WOM) DENGAN KETIDAKPUASAN PASIEN SEBAGAI VARIABEL INTERVENING (STUDI PADA PUSKESMAS NGESREP DI KOTA SEMARANG) - Suratman, Donni Renaldy; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2016)
This research was motivated by a lot of medical patient complaints after visiting to Puskesmas Ngesrep in form of critics and suggestions. It indicates there are unsatisfactory feelings after their visit to Puskesmas Ngesrep that could be because of disquality services from the management. This research is aiming to analyze the effect of disquality service medic and non-medic toward patient disatisfaction and negative WOM.This research using descriptive and quantitative for data analyze. The samples for this research are 400 patients that visited Puskesmas Nngesrep. Data was collected using questionnaires which tested the validity and reliability. The data was analyzed using multiple regression.The result of descriptive analysis shown that disquality service medic, disquality services non-medic, patient’s disatisfaction, and negative WOM Puskesmas Ngesrep classified as low. Statistical tests shown patient’s disatisfaction variable is affecting positively toward negatif WOM variable (hypothesis 1 is accepted), disquality service medic variable is affecting positively toward patient’s disatisfaction (hypothesis 2 is accepted), disquality services medic variable is affecting positively toward negatif WOM (hypothesis 3 is accepted), disquality service non-medic is affecting positively toward disatisfaction patient’s (hypothesis 4 is accepted), and disquality services non-medic variable is affecting positively toward intention to negative WOM (hypothesis 5 is accepted).